2008
DOI: 10.1109/mic.2008.122
|View full text |Cite
|
Sign up to set email alerts
|

Digging Deep into the Data Mine with DataMiningGrid

Abstract: As modern data mining applications increase in complexity, so too do their demands for resources. Grid computing is one of several emerging networked computing paradigms promising to meet the requirements of heterogeneous, large-scale, and distributed data mining applications. Despite this promise, there are still too many issues to be resolved before grid technology is commonly applied to large-scale data mining tasks. To address some of these issues, the authors developed the DataMiningGrid system. It integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Fig. 6 System architecture of execution engine [37] 3.3 DDM systems based on Grid DM in grid [13,30] computing environment represents a specific incarnation of DDM motivated by resource sharing via local and wide area networks [48]. Increased performance, scalability, access, and resource exploitation are the key drivers behind such endeavors.…”
Section: Ddm Systems Based On Meta-learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 6 System architecture of execution engine [37] 3.3 DDM systems based on Grid DM in grid [13,30] computing environment represents a specific incarnation of DDM motivated by resource sharing via local and wide area networks [48]. Increased performance, scalability, access, and resource exploitation are the key drivers behind such endeavors.…”
Section: Ddm Systems Based On Meta-learningmentioning
confidence: 99%
“…For highly domain-oriented end users, user transparency and ease-of-use is paramount. Technologyaware specialistsneed to control certain detailed aspects of DM and grid technology [48]. Today, new DDM projects aim to mine data in a geographically distributed environment which is based on grid standards and platforms, in order to hide the complexity of heterogeneous data and lower level details.…”
Section: Ddm Systems Based On Meta-learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Also ensemble learners are naturally suited for learning from distributed data sources. Also the DataMiningGrid.org project is concerned with all sorts of data mining applications on geographically distributed data sources (Stankovski et al, 2008). Another framework that is concerned with learning from distributed heterogeneous data sources is described by Caragea et al (2003) and has successfully been demonstrated for classification rule induction in the form of decision trees.…”
Section: Introductionmentioning
confidence: 99%